Fabrication and Physiochemical Properties of Alginate and Natural Aloe Vera Biofilm for Wound Healing Applications - BASKARAN, SIMRESAN; Binti Idris, Associate Professor Dr Maizlinda Izwana (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study fabricates and characterizes hydrogel films using sodium alginate and natural aloe vera for wound healing. Different ratios of alginate/aloe vera mixtures are investigated. The films are analyzed using SEM, FTIR, contact angle measurements, and AFM. The results show distinct microstructural features, additional active compounds, hydrophilic nature, and varying surface roughness. These findings highlight the potential of the hydrogel films for wound healing applications.